Survival Advantage of Lymphadenectomy in Patients with Ovarian Cancer. (9th August 2022) - Ignatov, Atanas; Hassan, Sheref Salim; Ivros, Stylianos; Papathemelis, Thomas; Ignatova, Zoya; Eggemann, Holm
Abstract: We investigated the survival effect of lymphadenectomy in ovarian cancer. The five-year progression-free and overall survival in early-stage ovarian cancer were not affected. Preliminary, unadjusted analysis in advanced ovarian cancer suggested an improvement in survival. However, after adjusting for other factors, e.g. ECOG performance status and patients' age, this survival advantage vanished. Our analysis suggests that systemic pelvic and para-aortic lymphadenectomy was not associated with an improvement of the progression-free and overall survival of patients with optimally debulked ovarian cancer.